2019
DOI: 10.1002/ece3.5510
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet irradiation increases size of the first clutch but decreases longevity in a marine copepod

Abstract: An important component of life history theory is understanding how natural variation arises in populations. Both endogenous and exogenous factors contribute to organism survival and reproduction, and therefore, it is important to understand how such factors are both beneficial and detrimental to population dynamics. One ecologically relevant factor that influences the life history of aquatic organisms is ultraviolet (UV) radiation. While the majority of research has focused on the potentially detrimental effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 69 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Moderate doses of UV exert several favorable effects such as induction of vitamin D biosynthesis (18), hormetic response in normal oral cells (19) and plant tissues (20,21), and increase in reproductive performance early in life (22).…”
Section: Discussionmentioning
confidence: 99%
“…Moderate doses of UV exert several favorable effects such as induction of vitamin D biosynthesis (18), hormetic response in normal oral cells (19) and plant tissues (20,21), and increase in reproductive performance early in life (22).…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet radiation is an important case of exogenous factor that is ecologically relevant for smallbodied invertebrates [9]. Over the past few decades, it has been well demonstrated that nature ultraviolet-B (UV-B) radiation increased signi cantly with the continuing depletion of stratospherico zone, which has becoming one of the grave concerns and most striking global changes [10,11].…”
mentioning
confidence: 99%
“…If these are not spheres, for instance if they are continuous tubes, we would expect some amount of variation in the cross sections, which we did not observe. The presence of one or two air layers throughout the exoskeleton could be advantageous to copepods by reflecting UV light and aiding in protection against UV radiation that is known to significantly influence survival and reproductive success in copepods that live in shallow splash pool habitats [41][42][43]. Carotenoids in both the body and eyespot additionally contribute to UV light absorption and, thereby, aid in UV protection.…”
Section: Discussionmentioning
confidence: 99%